Clinical researchPredictors of atrial fibrillation in patients following isolated surgical revascularization. A metaanalysis of 9 studies with 28 786 patients - Banach, Maciej; Misztal, Małgorzata; Goch, Aleksander; Rysz, Jacek; Goch, Jan Henryk (Archives of Medical Science, 2007)
Introduction: Atrial fibrillation (AF) is one of the most common complication following cardiac surgery AF significantly increases the length of intensive care unit and hospitalization stay and worsens the early and longterm prognosis. The purpose of our study was to apply metaanalysis methodology to find the most important risk factors that predict postoperative atrial fibrillation in patients undergoing isolated surgical revascularization of heart. Material and methods: After a careful review, nine studies met the inclusion criteria for the metaanalysis. A total of 28 786 patients were assessed in the metaanalysis. Results: Postoperative atrial fibrillation appeared in 7019 patients (24.4%), with mean age 67.1±2.9, among which there were 5283 men (75.3%) and 1736 women (24.7%). The age of patients without postoperative atrial fibrillation was lower (62.2±3.3), however the sex distribution was very similar (74.4% men vs. 25.6% women). The following predictors of postoperative atrial fibrillation (AF SCORE) were significant; advanced age (SMD 0.57), preoperative ejection fraction (SMD –0.12), the history of atrial fibrillation (OR 2.07), arterial hypertension (1.27), heart failure (1.47), peripheral vascular disease (1.37), chronic obstructive pulmonary disease (1.31), neurological event (1.44), renal failure (1.46), significant stenosis of left main coronary artery before the surgery (1.14), and postoperative use of inotropic therapy (1.76). Conclusions: The validated AF SCORE for developing postoperative atrial fibrillation may used to stratify patients undergoing surgical revascularization into high-risk and low-risk groups. It might be useful to appropriately target high-risk patients for aggressive prophylactic treatment in the preoperative period.